Factors Related To Heat Strain In Tough-Making Industry Workers In Kotabumi Selatan District, North Lampung District - Dony Mahendra; Nurul Aziza; Nana Novariana (PROFESSIONAL HEALTH JOURNAL, 2025)
Tofu industry workers are a group vulnerable to heat strain due to high heat exposure during work. Heat strains can cause serious health problems such as heat stroke, heat exhaustion, and heat cramps. Purpose This study aims to analyze the factors associated with heat strain in tofu industry workers in South Kotabumi District, North Lampung Regency in 2024. This study used a cross-sectional design. The population was all tofu industry workers in South Kotabumi District, North Lampung Regency. Samples were taken using total sampling technique, namely 30 workers. Data were collected through interviews, measurements, and observations. Data analysis was performed using univariate, bivariate using the Chi-square test, and multivariate using logistic regression test. showed that the factors associated with heat strain in tofu industry workers were heat stress (p=0.001), age ( P =0.003), gender ( P =0.007), and obesity ( P =0.012). Environmental heat stress, age, gender, and obesity are factors associated with heat strain in tofu industry workers. Heat strain control efforts need to be carried out, especially through improving the work climate and weight loss programs for obese workers.